Detection and Differentiation of vanC-1, vanC-2, and vanC-3 Glycopeptide Resistance Genes in Enterococci - Clark, Nancye C. (American Society for Microbiology, 1998)
The VanC phenotype, as found in Enterococcus gallinarum, E. casseliflavus, and E. flavescens, is characterized by intrinsic low-level resistance to vancomycin. The nucleotide sequences of the vanC-1 gene in E. gallinarum, the vanC-2 gene in E. casseliflavus, and the vanC-3 gene in E. flavescens have been reported, although there is some disagreement as to whether E. flavescens is a legitimate enterococcal species. Previous attempts to differentiate the vanC-2 and vanC-3 genes by PCR analysis have been unsuccessful. The purpose of the present study was to detect and differentiate the three vanC determinants and examine the distribution of these genes in a collection of both typical and atypical enterococci. The 796-bp vanC-1 PCR product was amplified only from E. gallinarum isolates. As expected, due to the extensive homology in the vanC-2 and vanC-3 gene sequences, all of the E. casseliflavus and E. casseliflavus/flavescens isolates produced the 484-bp vanC-2 PCR product, although the E. gallinarum isolates were negative. Only the E. casseliflavus/flavescens isolates produced the 224-bp vanC-3 product. Using the three sets of primers, we were able to detect and distinguish the vanC-1, vanC-2, and vanC-3 genes from both typical and atypical enterococci strains. Antimicrobial susceptibility tests and analysis of genomic DNA by pulsed-field gel electrophoresis were also performed, but the results indicated that they were not able to distinguish among strains possessing the three vanC genotypes.